Simultaneous quantification of lead, cadmium and zinc in superficial marine sediments using a carbon-fiber microelectrode modified with bismuth film - Fernández, Lenys (2023)
Marine sediments are a useful environmental assessment matrix as they naturally trap toxic substances of anthropogenic origin and thus have higher concentrations of these than the surrounding water. Therefore, developing methods for the sensitive, accurate, and inexpensive quantification of these substances is important, as the traditional techniques have various disadvantages. The current study evaluated the effectiveness of an in situ bismuth-modified carbon-fiber microelectrode (voltamperometric sensor) to simultaneously detect Pb, Cd, and Zn in marine sediments from Puerto Jeli in El Oro Province, Ecuador. This site is representative of the contamination levels present along the coast in this province. Differential pulse anodic stripping voltammetry was applied, and the resulting linear regression for the metal quantification ranged from 12 to 50 μg mL−1, with quantification limits for Pb(II), Cd(II), and Zn(II) of 18.69, 12.55, and 19.29 μg mL−1, respectively. Thus, the quantification with the sensor was successful. According to the preliminary results, Cd and Pb values exceeded the permissible limits established by Ecuador (Texto Unificado de la Legislación Secundaria del Ministerio del Ambiente) and the US Environmental Protection Agency, respectively.